Nursing Students Engagement in the Classroom and Clinical Practice - Nina Indriyawati; Dwi Yuwono Puji Sugiharto; Martono Martono; Muchsin Muchsin; Yuyun Setyorini; Rendi Editya Darmawan (Poltekkes Kemenkes Surakarta, 2022)
Background: The engagement of nursing students is very important and can affect their progress and success in the nursing profession in the future. The purpose of this research is to identify and explore the engagement of nursing students in the classroom and in clinical practice. Methods: This study used a systematic review design. This research used a database of indexed international journals such as Pubmed, Google Scholar, Science Direct, and BMC for the period 2011–2021 to search for research articles and analyze results using the PRISMA flow diagram. Research articles have been screened according to the inclusion criteria of this research, namely those containing student engagement or the engagement of nursing students in the classroom or clinical practice. Results: We obtained 12 research articles. Nursing students' engagement in the learning process takes place in two environments: the classroom and the clinical environment. Various studies on the engagement of nursing students showed a high level of engagement in the learning process that is influenced by various factors, including students, a student's relationships with other students, teachers, student-teacher/clinical instructor relationships, learning strategies, learning methods, and student relationships with the learning environment. Conclusion: The engagement of nursing students is important for their progress in their future profession because the level of engagement will lead to various short-term and long-term learning outcomes.